B-ACE Mobile Learning with Outcome-Based Education Approach: Developing ESP Learning Media for Airport Civil Engineering Students - Pratama, Raga Driyan; Jazera, Edelweis Silmi Eka; Putri, Ershanda Ardini; Fatmawati, Fatmawati; Kusumayati, Lusiana Dewi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study sought to develop prototype of B-ACE mobile learning application using Android operating system with an outcome-based education approach as a media to learn basic airport civil engineering. This study adopted the ADDIE development model. This study involved 72 aviation cadets of Airport Civil Engineering Department to complete the student needs analysis questionnaire and three lecturers who taught Basic English course in the department to complete the curriculum needs analysis questionnaire and conduct FGD. Results showed that the B-ACE prototype was developed through analysis, design, development, implementation, and evaluation stages. Experts showed valid scores without revision as the result of translational validity test (x̄ = 3.86), thus, the B-ACE mobile learning prototype was in accordance with the airside and landside materials and the outcome-based education curriculum applied in higher education. The students’ responses were positive after learning using B-ACE (x̄ = 98.8%).